The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acssuschemeng.1c05173
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus Quantum Dots as Hole Capturers in Group-VA Monoelemental Heterostructures for the Application of High-Performance Flexible Photodetectors

Abstract: Herein, black phosphorus (BP) quantum dots (QDs) with consistent sizes are loaded on bismuth (Bi) nanosheets (NSs) uniformly to serve as hole capturers in Group-VA monoelemental heterostructures via a facile sonication approach. The as-fabricated Bi NSs-BP QD-based photodetectors exhibit 4.6 μA/cm2 photocurrent density at applied 0.8 V bias potential, about 4.2 times enhancement compared to Bi NSs, which contributes to the construction of type-II heterojunctions that effectively restrain the recombination of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Y. Zhou et al also exhibited a superior flexible PD based on bismuth nanosheets-BP quantum dots heterojunctions by sonication-assisted LPE, achieving a photocurrent density of 4.6 mA cm À2 at an applied voltage of 0.8 V, and 100 nA cm À2 without external voltage. 145 (Fig. 9(b)) For the bending test, the device performance revealed the photocurrent density attenuation of 15% after 2000 times of bending and 8.8% under a bending angle of 601.…”
Section: Applicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Y. Zhou et al also exhibited a superior flexible PD based on bismuth nanosheets-BP quantum dots heterojunctions by sonication-assisted LPE, achieving a photocurrent density of 4.6 mA cm À2 at an applied voltage of 0.8 V, and 100 nA cm À2 without external voltage. 145 (Fig. 9(b)) For the bending test, the device performance revealed the photocurrent density attenuation of 15% after 2000 times of bending and 8.8% under a bending angle of 601.…”
Section: Applicationsmentioning
confidence: 98%
“…Copyright 2015, American Chemical Society. (b) Flexible Bi nanosheets-BP quantum dots PDs: (i) Device fabrication process, (ii) photocurrent density and responsivity, and (iii) temporal response 145. Reproduced with permission from 145.…”
mentioning
confidence: 99%
“…Meanwhile, the surface oxidation and chemical modification or ligand exchange of QDs can be used to adjust their photoelectric properties. 40 Lead chalcogenide QDs (PbS, PbSe, etc.) have been widely used as active materials of flexible PDs due to their adjustable bandgap, simple preparation method, low cost, and good compatibility with flexible substrates.…”
Section: Zero-dimensional (0d) Nanomaterialsmentioning
confidence: 99%
“…Meanwhile, the surface oxidation and chemical modification or ligand exchange of QDs can be used to adjust their photoelectric properties. 40…”
Section: Active Materials For Flexible Pdsmentioning
confidence: 99%
“…Among various QDs, metal-free QDs, especially those of pure elements, have attracted widespread research attention because of their low toxicity and excellent properties. Black phosphorus quantum dots (BPQDs) exhibit extraordinary catalytic potential by virtue of their superb electronic conductivity and abundant active sites, , which have been applied in numerous fields. Many investigations have indicated that the participation of BPQDs in the CL system has provided new avenues to promote the CL emission and expand the application range. It was found in our previous work that the catalytic effect of BPQDs can significantly boost lucigenin CL, suggesting that BPQDs are promising nanomaterials for CL research . Nonetheless, most of the current CL systems still require an alkaline environment to achieve high-quality CL performance. , It should be noted that the strong alkaline conditions lead to a low signal/noise ratio and poor universality of the systems.…”
Section: Introductionmentioning
confidence: 99%